Cold-chain logistics wireless supervision control device - TANG WENBING; JIANG QUANNENG (2015)
The utility model discloses a cold-chain logistics wireless supervision control device, and mainly solves the problem that in the prior art, all conditions of products cannot be comprehensively understood in real time by manufacturers. The cold-chain logistics wireless supervision control device comprises a transport tool used for transportation, an RFID temperature tag used for being disposed on a packing box body, a reader-writer used for identifying the RFID temperature tag, a central control system disposed on the transport tool and connected with the reader-writer, a wireless communication module connected to the central control system, and a cloud storage system communicated with the central control system via the wireless communication module; the transport tool is also provided with a monitor and a GPRS which are connected with the central control system; and the transport tool is also provided with a warning lamp connected with the central control system at a position adjacent to a transport operator. The cold-chain logistics wireless supervision control device is advantaged by comprehensive supervision, simple operation and low cost and the like.